Integrating High-Throughput Approaches and in vitro Human Trophoblast Models to Decipher Mechanisms Underlying Early Human Placenta Development - Lee, Bum-Kyu; Kim, Jonghwan (Frontiers in Cell and Developmental Biology, 2021)
The placenta is a temporary but pivotal organ for human pregnancy. It consists of multiple specialized trophoblast cell types originating from the trophectoderm of the blastocyst stage of the embryo. While impaired trophoblast differentiation results in pregnancy disorders affecting both mother and fetus, the molecular mechanisms underlying early human placenta development have been poorly understood, partially due to the limited access to developing human placentas and the lack of suitable human in vitro trophoblast models. Recent success in establishing human trophoblast stem cells and other human in vitro trophoblast models with their differentiation protocols into more specialized cell types, such as syncytiotrophoblast and extravillous trophoblast, has provided a tremendous opportunity to understand early human placenta development. Unfortunately, while high-throughput research methods and omics tools have addressed numerous molecular-level questions in various research fields, these tools have not been widely applied to the above-mentioned human trophoblast models. This review aims to provide an overview of various omics approaches that can be utilized in the study of human in vitro placenta models by exemplifying some important lessons obtained from omics studies of mouse model systems and introducing recently available human in vitro trophoblast model systems. We also highlight some key unknown questions that might be addressed by such techniques. Integrating high-throughput omics approaches and human in vitro model systems will facilitate our understanding of molecular-level regulatory mechanisms underlying early human placenta development as well as placenta-associated complications.